A stolen life : a memoir - Dugard, Jaycee Lee, 1980- (New York : Simon & Schuster, 2011)
The memoir of Jaycee Dugard, who was kidnapped on June 10, 1991, when she was 11 years old, and was missing--held prisoner by a registered sex offender--for over 18 years before her reappearance in 2009.
Keywords: Dugard, Jaycee Lee, -- 1980- -- Kidnapping, 1991; Kidnapping victims -- California -- Biography; Kidnapping -- California; Sexually abused children -- California -- Biography